Religious stories in transformation : conflict, revision and reception - Houtman, Alberdina. (Jewish and Christian Perspectives Series, 2016)
In Religious Stories in Transformation: Conflict, Revision and Reception , the editors present a collection of essays that reveal both the many similarities and the poignant differences between ancient myths in Judaism, Christianity, Islam, and modern secular culture and how these stories were incorporated and adapted over time. This rich multidisciplinary research demonstrates not only how stories in different religions and cultures are interesting in their own right, but also that the process of transformation in particular deserves scholarly interest. It is through the changes in the stories that the particular identity of each religion comes to the fore most strikingly.